Formation and Evolution of Cellular Structures in Wedge-Induced Oblique Detonations - Chengxuan Yu; Zhenye Luan; Hua Jin; Yue Huang; Yancheng You (International Journal of Aerospace Engineering)
Numerical simulation of an oblique detonation induced by a wedge is performed to investigate the formation and evolution of the oblique cellular detonation structure and the quantitative comparison of the cellular structure of a normal and an oblique detonation. The compressible reactive Euler equations are solved using the seventh-order WENO scheme on an adaptive mesh based on the open source program Adaptive Mesh Refinement in Object-oriented C++ (AMROC). The numerical results show that there are two sets of transverse waves, the left-running transverse waves (LRTW) and the right-running transverse waves (RRTW), which form the oblique cellular detonation structure. Although both sets of transverse waves are convected downstream, they propagate at almost the same relative velocity in the opposite direction. The LRTWs start in the transition zone because of the detonation instability. However, the RRTWs form due to the interaction between the deformed detonation front and the reflected shock wave from the wedge. For the same degree of overdrive, numerical simulations reveal that the characteristic cell size of an oblique detonation is almost the same as that of a normal detonation.